Usage, Risk, and Benefit of Weight-Loss Drugs in Primary Care - Tomas Forslund; Pauline Raaschou; Paul Hjemdahl; Ingvar Krakau; Björn Wettermark (Hindawi Limited, 2011)
Purpose. To investigate the use of the weight-loss drugs rimonabant, sibutramine, and orlistat in primary care and to characterize the patients receiving the drugs. Methods. In this retrospective, descriptive study, 300 randomly selected patients having started weight-loss drug treatment at 15 primary care centres were investigated using the patient's medical records and their complete drug purchase data. Results. Even though 48% of the patients specifically demanded drug treatment, 77% continued treatment less than one year. 28% of rimonabant patients and 32% of sibutramine patients had a history of depression or antidepressant treatment. 41% of sibutramine patients had a history of hypertension and/or cardiovascular disease. 36% had no documented weight after treatment initiation. Conclusions. These results suggest that weight-loss drug treatment was often initiated upon patient request but was of limited clinical benefit as it was managed in a large portion of Swedish primary carecenters.